ANALISIS PERAN PEMUDA KRISTEN DAN KATOLIK DALAM MEMBANGUN SPIRITUALITAS DI ERA DIGITAL - Yosefo Gule (Bahasa Indonesia, 2022)
This article aims to describe how the role of Christian and Catholic youth in building their spirituality in their community. The results of the study show that the media has a very large influence on the spiritual growth of the Christian and Catholic youth generations. There are many young people whose lives are damaged and their spiritual level is low because they are influenced by social media. In this case the church needs to address this problem, especially to youth and youth as the biggest users. On the other hand, social media is also a tool that God can use to guide young people in repentance or good spiritual growth. In this case, the role of Christian and Catholic youth is to use digital spaces as a service, to reach out to their fellow communities, to relate to other people around them; maintain the privacy of any sensitive personal data and information; able to guard every word and deed, both in cyberspace and in the real world; can do cyber theology so that their faith community has spiritual intelligence; able to encourage changes in motivation in social media and actualize themselves in the digital world according to Christian ethics; Extrinsic motivation in the life of the church undergoes transformation and strong Christian and Catholic youth community and communication between generations are healthy. The research method in writing this article uses a descriptive qualitative study method with a library research approach.